Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone please explain to me how to differentiate this function?

$$90 + 45 \cos(t^2/18)$$

I know you use the chain rule, but I can't get the final result correct.

share|cite|improve this question
up vote 3 down vote accepted

$$\zeta(t)=90+45\cos\left(\frac{t^2}{18}\right)$$ $$\require{cancel}\begin{align} \frac{d\zeta}{dt}&=\cancelto{0}{\frac{d}{dt}(90)}+\frac{d}{dt}\left(45\cos\left(\frac{t^2}{18}\right)\right)\\&= \frac{d}{dt}\left(45\cos\left(\frac{t^2}{18}\right)\right) \\&=45\left(-\sin\left(\frac{t^2}{18}\right)\right)\underbrace{\left(\frac{d}{dt}\left(\frac{t^2}{18}\right)\right)}_{\frac{t}{9}}\\& =-5t\sin\left(\frac{t^2}{18}\right)\end{align}$$

Because: $$\frac{d}{dx}\cos(\varphi)=-\sin(\varphi)\cdot\frac{d\varphi}{dx}$$

share|cite|improve this answer
thank you this made so much sense! Splitting up the equation helped me see what i had to differentiate. The 1/9 was were I went wrong and messed up. Thanks!!! – sloth1111 May 7 '14 at 0:24
@sloth1111 No problem. Good luck. – Shahar May 7 '14 at 0:25

Here by using the chain rule:


share|cite|improve this answer

Well the $90$ becomes simply zero. So you have $$45\left(f\left(g(t)\right)\right)'$$ where $g(t)=t^2/18$ and cos $f(x)=\cos(x)$. The chain rule goes: $$\left(f\left(g(t)\right)\right)'=f'(g(t))\cdot g'(t)$$ And $f'(x)=-\sin(x)$ so $f'(t^2/18)=-\sin(t^2/18)$. and $g'(t)=t/9$, that's clear, right?

So $$45\cdot f'(g(t))\cdot g'(t)=-45\cdot\sin(t^2/18)\cdot t/9$$

share|cite|improve this answer

$\frac{d}{dt}90 = 0$ so we concentrate on your second term.

$\displaystyle\frac{d}{dt} \cos(t^2/18) = \frac{dt^2}{dt}\frac{d}{dt^2} \cos(t^2/18) = 2t \times (-\frac{1}{18}\sin(t^2/18))= -\frac{1}{9}t\sin(t^2/18)$

And then multiply by 45.

When you take the derivative of the $\cos()$, think of $t^2$ as a variable in its own right (which it really is, after all). If it helps, replace it with another symbol, like $t^2 = u$, and then, when you have your result, put the $t^2$ back in where you have $u$.

share|cite|improve this answer

Remark that $cos'(t)=-sin( t)$ and $\frac{d}{dt}(\frac{t^2}{18})=\frac{t}{9}$. Then $$ \frac{d}{dt}(90+45cos(\frac{t^2}{18}))=\frac{d}{dt}(90)+\frac{d}{dt}(45cos(\frac{t^2}{18}))=0+45\frac{d}{dt}(cos(\frac{t^2}{18})) $$ But setting $s=s(t)=\frac{t^2}{18}$, $$ \frac{d}{dt}(cos(\frac{t^2}{18}))=\frac{d}{ds}(cos(s))\frac{d}{dt}(s(t))=-sin(s).s'(t)=-sin(\frac{t^2}{18})\frac{t}{9}. $$ Thus $$ \frac{d}{dt}(90+45cos(\frac{t^2}{18}))=45(-sin(\frac{t^2}{18})\frac{t}{9})=-5t.sin(\frac{t^2}{18}) $$

share|cite|improve this answer

You need to see the nesting:

$$ f(t) = 90 + 45\cos\left(\frac{t^2}{18}\right) \\ g(x) = 90 + 45\cos(x) \rightarrow g\left(x = \frac{t^2}{18}\right) = f(t) = 90 + 45\cos\left(\frac{t^2}{18}\right) \\ g'(x) = 90 - 45\sin(x) \rightarrow g'\left(x = \frac{t^2}{18}\right) = 90 - 45\sin\left(\frac{t^2}{18}\right) \\ x'(t) = \frac{d}{dt}\left(\frac{t^2}{18}\right) = \frac{t}{9} \\ \left.\left.\frac{d}{dt}\right(f(t)\right) = \left.\left.\frac{d}{dt}\right (g\left(x(t)\right)\right) = \frac{dx}{dt}\cdot\left(\frac{dg}{dx} \circ x(t)\right) \\ \frac{df}{dt} = \frac{t}{9}\left(90 - 45\sin\left(\frac{t^2}{18}\right)\right) $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.